Legal Protection of Children as Victims of Domestic Violence - Pasaribu, Robby Naldo Shunan; Hasibuan, Aulia Rahman Hakim (International Journal of Health, Economics, and Social Sciences (IJHESS), 2025)
This study aims to discuss the legal basis for child protection as a victim of domestic violence (KDRT) and examine the legal protection policy by the state for children who are victims of domestic violence. A type of normative juridical research, which discusses certain legal phenomena and analyzes them based on laws regulations, and norms that live in society. The results of this study show that the legal regulation of children as victims of domestic violence is regulated in Law Number 35 of 2014 concerning Child Protection, Law Number 23 of 2004 concerning the Elimination of Domestic Violence, and Law Number 11 of 2012 concerning the Child Criminal Justice System. Legal policies for children who are victims of domestic violence include: physical and psychological protection, legal assistance, social and psychological rehabilitation, as well as protection in the legal and judicial process. This protection not only ensures protection like a child but also comprehensive recovery or rehabilitation.